USM – COLUMBIA UNIVERSITY TO MONITOR SHIFTS IN NATION’S WEATHER - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 24 August 2015 – The Centre for Global Sustainability Studies (CGSS) Universiti Sains Malaysia (USM), in cooperation with Columbia University New York would continue to monitor and file reports on ongoing weather conditions to the authorities concerned in facing the possibility of another flood disaster in the country.